Studi Waktu Perjalanan dan Tundaan Rute Danau Sunter-Mall Kelapa Gading - Nofrida Nos (CV. Ulil Albab Corp, 2023)
Danau Sunter Selatan Road is the name of one of the roads in North Jakarta, specifically in the Sunter area. This road connects the Kelapa Gading area through two roads, namely Mitra Sunter Boulevard Road and Yos Sudarso Road. Meanwhile, Boulevard Barat Kelapa Gading Road is the name of one the roads located in the Kelapa Gading area of North Jakarta. Both of these roads often experience traffic jams or delays during peak hours, so researchers wanted to conduct research on these to roads. The purpose of this study is to find out how the travel time is on the Danau Sunter Selatan Road section and Boulevard Barat Kelapa Gading Road and also to find out what factors cause delays on the two road sections. Research data collection conducted from July 3 to July 7, 2023 is in the form of travel time data, delays, vehicle speeds, and traffic volumes. From the results of collecting this data, it was found that the longest travel time occurred on July 4, 2023 at 16.00 – 17.00 with a total time traveled for 35 minutes 58 seconds with the lowest vehicle speed being 38 km/ hour, while the highest traffic volume occurred on July 7 at 17.00 – 18.00 Kelapa Gading direction with a total number of vehicles passing through the studied road sections of 8795.